2020
DOI: 10.1108/jmd-07-2020-0233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leader-member exchange ambivalence on work attitudes: a moderated mediation model

Abstract: PurposeThis study examines whether the relationship between ambivalence in leader-member exchange (LMX) and career commitment is influenced by organizational embeddedness as a mediating variable. There is also an investigation of when and to what extent job strain influences the conditional indirect effect between LMX ambivalence on career commitment via the mediator.Design/methodology/approachData were collected from 1,134 accountants working in various disciplines. The PROCESS macro and a bootstrapping proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 55 publications
(119 reference statements)
1
17
0
3
Order By: Relevance
“…The ambiguous intimacy ( ) of the leadership is the root cause of the leader–member ambivalence; subordinates do not adequately have a united front with the leader and tend to take conservative or even stagnant approaches to performing their tasks [ 4 ]. Dechawatanapaisal [ 41 ] proposed that employees’ ambivalence has a direct impact on career commitment. Wu et al [ 42 ] revealed that employees tend to adopt compromised approaches whether actively coping or passively avoiding such ambiguous intimacies.…”
Section: Methodsmentioning
confidence: 99%
“…The ambiguous intimacy ( ) of the leadership is the root cause of the leader–member ambivalence; subordinates do not adequately have a united front with the leader and tend to take conservative or even stagnant approaches to performing their tasks [ 4 ]. Dechawatanapaisal [ 41 ] proposed that employees’ ambivalence has a direct impact on career commitment. Wu et al [ 42 ] revealed that employees tend to adopt compromised approaches whether actively coping or passively avoiding such ambiguous intimacies.…”
Section: Methodsmentioning
confidence: 99%
“…According to a meta-analysis (Ilies et al, 2007), a high LMX level can reduce turnover intention. Furthermore, high-quality exchanges between leaders and subordinates increase job embeddedness (Amoah et al, 2021;Dechawatanapaisal, 2021). Conversely, in low-quality LMX, subordinates are considered "outsiders" and have less than ideal social interaction (Dechawatanapaisal, 2018b(Dechawatanapaisal, , 2021.…”
Section: Relationship Between Lmx and Turnover Intentionmentioning
confidence: 99%
“…Furthermore, high-quality exchanges between leaders and subordinates increase job embeddedness (Amoah et al, 2021;Dechawatanapaisal, 2021). Conversely, in low-quality LMX, subordinates are considered "outsiders" and have less than ideal social interaction (Dechawatanapaisal, 2018b(Dechawatanapaisal, , 2021. Based on this description, the following hypothesis is proposed: H 2 : LMX has a negative impact on turnover intention.…”
Section: Relationship Between Lmx and Turnover Intentionmentioning
confidence: 99%
See 2 more Smart Citations